2005
DOI: 10.1103/physrevb.71.125304
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscopic phonon transmission through a nanowire-bulk contact

Abstract: We calculate the frequency-dependent mesoscopic acoustic phonon transmission probability through the abrupt junction between a semi-infinite, one-dimensional cylindrical quantum wire and a three-dimensional bulk insulator, using a perturbative technique that is valid at low frequency. The system is described using elasticity theory, and traction-free boundary conditions are applied to all free surfaces. In the low-frequency limit the transmission probability vanishes as 2 , the transport being dominated by the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 18 publications
3
46
0
Order By: Relevance
“…In the low temperature regime (T < 50 K) the interface area normalized contact conductances collapse to a single curve and display a temperature dependence of T 3 . This trend was formerly predicted analytically 32 and confirmed in experiments 33 , where it was shown that deviations from the T 3 behavior stem from specific features of the SiNW, such as surface roughness, the effects of which add up in series to the contact conductance. On the other hand we observe that the reflection spectrum (not shown), scales with the linear dimension of the contact interface, which seems to indicate that back scattering of phonons mostly happens at the perimeter of the junction.…”
Section: Resultssupporting
confidence: 67%
“…In the low temperature regime (T < 50 K) the interface area normalized contact conductances collapse to a single curve and display a temperature dependence of T 3 . This trend was formerly predicted analytically 32 and confirmed in experiments 33 , where it was shown that deviations from the T 3 behavior stem from specific features of the SiNW, such as surface roughness, the effects of which add up in series to the contact conductance. On the other hand we observe that the reflection spectrum (not shown), scales with the linear dimension of the contact interface, which seems to indicate that back scattering of phonons mostly happens at the perimeter of the junction.…”
Section: Resultssupporting
confidence: 67%
“…[6] The interplay between the RSOI and DSOI leads to a significant change in the transport property. There are a few works on the effects of the competition between these two types of SOI on the transport properties of 2DEG, [7,8,9]especially in mesoscopic rings [10]. The circular photogalvanic effect can be used to separate the contribution of the RSOI and DSOI, and the relative strengths of the RSOI and DSOI can be extracted from the photocurrent.…”
Section: Introductionmentioning
confidence: 99%
“…We can choose a new basis vector such that the charge Hall conductance vanishes [34], however, the physics conclusion Eq. (30) [see also Eq.…”
Section: Berry Phase and Spin Currentmentioning
confidence: 99%